Social and Cultural Context in Learning Aqidah Akhlak - Julia, Arini; Putri, Kilsi Rusta; Anggraini, Lely; Wijayanti, Milanisti Eki; Pratama, M Ajhi (Global Education Journal, 2025)
This study examines the social and cultural contexts that shape the effectiveness of Aqidah Akhlak learning in Indonesia’s multicultural society, where diverse traditions simultaneously support and challenge the internalization of Islamic values. The research aims to analyze how local culture influences students’ religious understanding, identify the pedagogical challenges teachers face in pluralistic environments, and formulate responsive strategies to strengthen faith and moral education. Using a qualitative literature review method, the study synthesizes findings from books, accredited national journals, and recent international research related to Islamic education, multiculturalism, and contextual learning. The results reveal that local cultural values such as cooperation, respect, and communal harmony reinforce Islamic moral concepts, whereas syncretic practices and mystical beliefs may hinder the development of pure monotheistic understanding. Teachers therefore function as cultural interpreters, role models, and facilitators of contextual learning who bridge Islamic teachings with students’ sociocultural realities. The study concludes that integrating sociocultural awareness, exemplary conduct, and contextual strategies can enhance the relevance and meaningfulness of Aqidah Akhlak learning. Its primary contribution lies in offering a conceptual model that links multicultural pedagogy, contextual teaching, and Islamic moral formation, providing a foundation for developing culturally responsive Islamic education.Bottom of Form